LEMBAR KERJA SISWA (LKS) BERBASIS GUIDED INQUIRY UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS SISWA SMP - Shokhib Zaky Fananto; Tutut Nurita (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
This study aimed to describe the effectiveness of students worksheet based guided inquiry to facilitate students critical thinking skills by knowledge test and student questionnaire responses. The trial design in this study was a pre-experimental One Group Pretest-Posttest. The instruments used were the pre-test and post-test questions of critical thinking skills and student questionnaire responses. The sample of this study was 38 7th grade students in a school in Surabaya. The results of the critical thinking skills test students obtained an N-Gain score from the indicator gave a simple explanation of 0.79 with high criteria; build basic skills of 0.81 with high criteria; and concluded of 0.76 with high criteria. The results of the questionnaire responses from students showed 93.20% of students gave a positive response to the students worksheets with very effective criteria. Based on the research that has been done, then it can be concluded that students worksheet based guided inquiry get to facilitate students critical thinking skills.